2004
DOI: 10.3122/jabfm.17.4.235
|View full text |Cite
|
Sign up to set email alerts
|

Controlled-Release Methylphenidate Improves Attention During On-Road Driving by Adolescents with Attention-Deficit/Hyperactivity Disorder

Abstract: Background: Attention-deficit/hyperactivity disorder (ADHD) is associated with a 3-to 4-fold increase in both driving-related accidents and associated injuries. Methylphenidate (MPH) is the most commonly prescribed psychostimulant medication for ADHD. It has been demonstrated to improve performance on a driving simulator. This study investigated whether a once-daily, long-acting, osmotic, controlledrelease MPH formulation improves the driving performance of ADHD adolescents while driving their own car on an ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
45
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 19 publications
(17 reference statements)
6
45
0
2
Order By: Relevance
“…Surveys have found an increased probability of driving accidents among those with conditions ranging from, for example, attention deficit hyperactivity disorder (ADHD; Barkley, Guevremont, Anastopoulos, DuPaul, & Shelton, 1993;Murphy & Barkley, 1996), to diabetes (Cox et al, 2003), to dementia (Carr, Duchek, & Morris, 2000;Zuin, Ortiz, Boromei, & Lopez, 2002), to heart disease (McGwin, Sims, Pulley, & Roseman, 2000), to arthritis (McGwin et al, 2000), and to emotional stress (Lagarde et al, 2004). Yet studies with such populations using on-road methods to measure driving behaviors may place both participants and researchers at increased risk for harm (Cox, Humphrey, Merkel, Penberthy, & Kovatchev, 2004). On-road behavior evaluations also lack the replicability, control, efficiency, safety, and ease of use associated with simulated driving experiments, in turn making inferences about the impact of experimental manipulations on driving behavior more difficult (Godley, Triggs, & Fildes, 2002).…”
mentioning
confidence: 99%
“…Surveys have found an increased probability of driving accidents among those with conditions ranging from, for example, attention deficit hyperactivity disorder (ADHD; Barkley, Guevremont, Anastopoulos, DuPaul, & Shelton, 1993;Murphy & Barkley, 1996), to diabetes (Cox et al, 2003), to dementia (Carr, Duchek, & Morris, 2000;Zuin, Ortiz, Boromei, & Lopez, 2002), to heart disease (McGwin, Sims, Pulley, & Roseman, 2000), to arthritis (McGwin et al, 2000), and to emotional stress (Lagarde et al, 2004). Yet studies with such populations using on-road methods to measure driving behaviors may place both participants and researchers at increased risk for harm (Cox, Humphrey, Merkel, Penberthy, & Kovatchev, 2004). On-road behavior evaluations also lack the replicability, control, efficiency, safety, and ease of use associated with simulated driving experiments, in turn making inferences about the impact of experimental manipulations on driving behavior more difficult (Godley, Triggs, & Fildes, 2002).…”
mentioning
confidence: 99%
“…Preliminary data is emerging in nonmedical categories of performance. Methylphenidate has been shown to decrease errors from inattentive driving in adolescents with attention-deficit hyperactivity disorder [5]. Whether methylphenidate or other stimulants could decrease performance errors by those without the disorder or by physicians is an untested question.…”
Section: The Case For Enhancementmentioning
confidence: 99%
“…Five controlled studies have found that active treatment of ADHD with stimulant medications significantly improved on-road and simulator driving performance (Barkley, Murphy, O'Connell, & Connor, submitted;Cox, Merkel, Kovatchev, & Seward, 2000;Cox, Humphrey, Merkel, Penberthy, & Kovatchev, 2004;Cox, Merkel, Penberthy, Kovatchev, & Hankin, 2004). Ganz and colleagues found that driving reaction time on a driving simulator worsened 1 week after total hip arthroplasty but then subsequently improved, leading them to recommend patients wait 4 to 6 weeks after surgery before resuming driving (Ganz, Levin, Peterson, & Ranawat, 2003).…”
Section: Medical Interventions and Drivingmentioning
confidence: 99%